PENERAPAN METODE PEMBELAJARAN TERBIMBING DALAM MENINGKATKAN KEMAMPUAN SISWA KELAS X IPA SMA NEGERI 1 TINOMBO SELATAN MENULIS SURAT PRIBADI - Nasim Taha; Al-Afandi Al-Afandi (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
The main problem in this study is the low learning outcomes of students of class X IPA SMA Negeri 1 Tinombo Selatan on the material of writing personal letters. There are several things that cause these problems, including: 1) students do not understand the concepts being taught and 2) the methods used by teachers in carrying out learning make students less active, also of course other factors. This research was conducted with the aim of improving the ability of students of class X IPA SMA Negeri 1 Tinombo to write personal letters through the guided practice method. Benefits Improve student learning outcomes, especially learning to write personal letters and hone the ability to work alone through exercises under the guidance of the teacher, and do not feel neglected by the teacher because they are still monitored in carrying out their duties. The method used in this research is descriptive method. The design of this study refers to the Kemmis and Mc Taggart model which consists of four components, namely 1) planning, 2) action implementation, 3) observation and 4) reflection. The data collected in this study is in the form of teacher and student activity data during the learning process obtained by using observation sheets and student learning outcomes data obtained by giving individual tests to students. In the research that has been carried out, it was found that the students of class X IPA SMA Negeri 1 Tinombo Selatan experienced an increase in classical absorption from the pre-action results of 90%